Junction between Z and B conformations in a DNA restriction fragment: evaluation by Raman spectroscopy. - Wartell, R M (1982)
Raman vibrational spectra were obtained from two DNA restriction fragments and the DNA polymer (dG-dC)n . (dG-dC)n in 0.01 and 4.5 M NaCl. One fragment contained 95 base pairs (bp) of the Escherichia coli lactose operator-promoter region (95-bp fragment). The other fragment consisted of the 95-bp region flanked by 26 and 32 bp of dC-dG sequences and BamHI ends (157-bp fragment). In 0.01 M NaCl all three DNAs have Raman spectra characteristic of a right-handed B conformation. The high salt spectrum of the 95-bp fragment is also characteristic of a B conformation. However, the spectrum of the 157-bp fragment in 4.5 M NaCl shows major intensity changes from the 0.01 M NaCl spectrum. These changes are also observed in the high salt spectra of (dG-dC)n . (dG-dC)n and are correlated with the presence of a left-handed Z conformation. Comparisons between the high salt Raman spectra of the 157-bp fragment and spectra calculated from (dG-dC)n . (dG-dC)n and the 95-bp fragment indicated that essentially all of the dC-dG regions in the 157-bp fragment are in the Z conformation and a large part (approximately 80%) of the 95-bp region no longer has a B-type backbone vibration. However, this non-B-DNA-like character of the central region is not indicated by base vibrations.